G42 Holding children still for clinical procedures; an international survey of health professionals reported practice. (24th May 2017) - Bray, L; Carter, B; Ford, K; Dickinson, A; Waters, T
Abstract : Aim: This paper will present an international perspective on health professionals' reported practice of holding children still for clinical procedures. Methods: A short electronic survey was distributed internationally to child health professionals through network sampling. The survey focused on the reported practice of children being held still for procedures such as cannulation, investigations or medication administration. Holding in response to challenging behaviour arising from a child's mental health or learning disability was not the focus of this study. The survey included closed questions and scenarios of clinical procedures to prompt open text responses. This presentation will focus on the structured elements of the questionnaire. Data were analysed using descriptive statistics. Results: 1106 surveys were returned from health professionals working in a range of countries (including Australia, New Zealand and the UK) and job roles (doctors, nurses, allied health professionals and play specialists). Most of the health professionals identified that children were held within their health setting either quite often or very often for clinical procedures (81%, n=676/828). Professionals reported that if a child was to be held for a procedure within their setting this would most often be undertaken by parents (63%, n=554) and/or nurses (26%, n=230). The majority of professionals had not received any training relating to holding children still for procedures (61%, n=533) and were unaware of any guidance and/or policies which may govern their practice (62%, n=589). Permission to hold children for procedures was gained verbally from parents (77%, n=500) and children (43%, n=277), although some professionals stated that permission was not required from parents (17%, n=111) or children (40%, n=258) for holding to take place. Conclusion: Health professionals from different disciplines, countries and care settings report similar practices of children being held still for procedures. Children are reported as being frequently held in order for procedures to be completed. Professionals report a lack of training and guidance in how to proceed when a child is uncooperative before and during a procedure and a wide variation in how they gain permission from children and parents for holding to take place.